Safety of Small, Rural Dams and Barrier Lake Management - Palmieri, Alessandro (World Bank, Washington, DC, 2012)
This note provides lessons learned and recommendations for artificial dams and barrier lakes following an earthquake. In the case of artificial dams, emphasis has been placed on small, rural dams rather than on larger, well-engineered dams because smaller dams represent a higher hazard in China. That higher risk from smaller dams is also confirmed by international experience. Barrier lakes and their management are highlighted as they are formed as a specific outcome of earthquakes. Key issues and lessons learned from international experience are presented with reference to three case studies of relevant World Bank-supported projects: Gujarat earthquake-dam safety aspects; and the Armenia dam safety program. Brief descriptions of these projects are provided in annexes at the end of the note, and further information is available at the request of the National Development and Reform Commission (NDRC).